English Teachers’ Perceptions on the Use of Technology-Based Media in Teaching English during Covid-19 Pandemic: A Descriptive Study at SMA N 9 Padang - Olaff Yoki Ardena; Sitti Fatimah (Journal of English Language Teaching, 2021)
Digital media is a blend of technology and content, and building digital media products requires teams of professionals with diverse skills, including technical skills, artistic skills, analytical and production of coordination skills. All of these skills need to be balanced on a team, with all team members focused on creating the best user experience. This study is limited to focusing on teachers in the use of digital-based technology media in English learning in Senior High School. The instruments of this research were a questionnaire test and a teacher’s perception questionnaire. The test consisted of 50 questions and the questionnaire consisted of four indicators of the benefits of the teachers. The population of this research is the teachers of SMAN 9 Padang. The result shows that technology media more effective for English teachers. The mean score on the questionnaire was 1.02.